Fabrication and optical characterization of nanoparticles in liquid media. - Zamiri, Reza (2011)
In the present study we have investigated the fabrication of metal nanoparticles (NPs)using Laser Ablation (LA) technique and measured the thermal and non-linear optical properties of nanofluids. A big challenge in the synthesis of NPs is particle agglomeration. This tendency can be inhibited by stabilization of NPs with chemical species and therefore, much effort has been undertaken to use different materials as colloidal stabilizers. We performed LA to metal plate in chitosan solution, starch aqueous solutions and various vegetable oils to prepare metal NPs. It was revealed that the generation as well as the stability of NPs was increased in comparison with LA in water. The results suggested that the increased NPs generation is attributable to increased secondary etching efficiency by the solvent confined plasma toward the plate. On the other hand, the size decrease of the NPs was remarkable. The effects of ablation time and frequency in some cases were also studied. NPs appear to be ideally suited for applications in targeted thermal effects in medical therapies and photothermally activated drug delivery; all depend critically on the thermal transport between the NPs and the surrounding liquid. In this second part of work, thermal lens spectroscopy was used to determine the thermal diffusivity of Copper and Silver NPs in polyvinyl pyrrolidone prepared by gamma radiation method and thermal diffusivity of clay containing Silver NPs prepared by UV-irradiation and chemical reduction methods. The effect of size and concentration of NPs on thermal diffusivity of nanofluid was also studied. The obtained results showed that the thermal diffusivity of nanofluids increases with the increase of metal NPs concentration. We studied the effect of nanoparticle size on thermal diffusivity of silver nanofluid containing silver nanoparticles in polyvinylpyrrolidone. The obtained result showed a decrease of the thermal diffusivity of nanofluid with the decrease of particle size. We attributed this decrement in thermal diffusivity to phonon scattering at interface of particles-liquid and poor contact between the nanoparticles and surrounded liquid. The thermal diffusivity of fluids containing Cu-NPs was measured by pulsed laser thermal lens technique. The obtained results showed that the rapid electron-phonon scattering of NPs causes the thermal diffusivity of the solutions increases with the increase of Cu-NPs density. Materials with high non-linear refractive index are always of huge interests for their potential applications on many non-linear optical devices. Composite systems containing metal NPs such as Silver, Gold, and Copper also have high non-linear refractive index because of metal NPs unique ability to support surface plasmon resonance at visible wavelengths. In this study the investigation of non-linear optical properties of media such as clay, palm oil, monoolein, starch, and polyvinyl pyrrolidone containing metal NPs is presented. The obvious spatial self-phase modulation and the influence of thermal-induced negative lens are observed when a beam propagates through these solutions, indicating promising applications such as optical limiting and beam flattening. The obtained results showed that the addition of NPs inside the fluids can induce strong non-linear optical properties due to the presence of surface plasmon peak in visible region. The nonlinear optical properties of prepared Ag-NPs in Monoolein and Palam oil have been studied using Z-scan, and spatial self phase modulation techniques. The samples displayed nonlinear optical properties which strongly depend on volume fraction of particles into the Monoolein solutions